- Penerapan Strategi Pendinginan Pasif pada Bangunan Masjid Pathok Negoro di Yogyakarta: - - Handoko, Jarwa Prasetya Sih (UII, 2024)
Passive cooling strategy in building design is one of the applications of climate responsive architecture concept. Tropical climate areas have abundant solar radiation potential so that it can be utilized optimally for air conditioning in buildings. Traditional architecture is one of the architectural styles formed from the long process of our ancestors adapting to natural conditions including local climate conditions, one of which is traditional Javanese architecture. Pathok Negoro Mosque in Yogyakarta is a mosque with traditional Javanese architectural style which is managed and fostered by the Yogyakarta Sultanate Palace. The purpose of this study is to determine the application of a passive cooling strategy in the Pathok Negoro Mosque building in Yogyakarta as a building in a hot humid tropical climate area and the results can be used as a reference for adaptive design with Hot Humid Tropical Climate conditions. This study uses a qualitative descriptive method, by reviewing and understanding the theory related to passive cooling which will be the basis for analyzing the selected case study building. The results of this study are that the passive cooling strategy applied is sunshade, selection of wall materials according to climate characteristics, natural ventilation, placement of atria and central lobbies, and openings in the mosque porch. In addition, the Plosokuning, Mlangi, and Wonokromo Mosques implement an evaporative cooling strategy and place the veranda as an intermediate space.